PELATIHAN BACA TULIS AL-QUR’AN UNTUK REMAJA PESANTREN: MEMBANGUN GENERASI QUR’AN DI ERA DIGITAL - Najiburrohman; Ismail Marzuki; Sabilatul Hidayah (SINAR: Sinergi Pengabdian dan Inovasi untuk Masyarakat, 2024)
Miftahul Ulum II is one of the institutions in Sumber Logan Islamic Boarding School. Until now, this institution has a very high concentration on the sciences of the Qur'an, such as learning to sound the letters according to their place of release, according to the rules of tajweed and writing them. Of course, this level is the earliest level and determines the success of learning the Qur'an at the next level. This training aims to provide knowledge, abilities, and skills to read and write the Qur'an to students with effective Qur'an learning methods. The method of implementing this training is carried out through several stages, including the pre-activity stage, the implementation stage with an educational and participatory approach, and the evaluation stage which is intended to assess the results of this training activity. The results of the training show that the training on reading and writing al-Qur'an organized at the Sumber Logan Islamic Boarding School has a significant impact on the ability and skills of reading and writing al-Qur'an of students. This is evidenced by the results of the pretest and post test during this training activity. With 3 main materials in the field of reading the Qur'an and 3 main materials in the field of writing the Qur'an, the ability of the trainees increased quite dramatically, from the initial pretest results there were only 8 or 30% of participants who had good predicates in the aspect of reading the Qur'an, after the post test it increased to 17 or 62.96% of participants with good predicates in the same aspect. While for the aspect of writing skills al-Qur'an, from the pretest results there were only 5 or about 19% of participants who had good predicates, after the training there were 14 or 51.85% of participants whose writing skills had increased.